Redox-responsive crown ethers containing a direct link between the ferrocene redox-active centre and a benzo-crown ether. Crystal structures of a ferrocene benzo-15-crown-5 ligand and of its sodium complex - Beer, P; Sikanyika, H; Blackburn, C; McAleer, J; Drew, M (1990)
New redox-active crown ethers, 15-ferrocenyl-2,3,5,6,8,9,11,12-octahydro-1,4,7,10,13- benzopentaoxacyclopentadecine (L1) and N-(4-ferrocenylphenyl)-1,4,7,10-tetraoxa-13-azacyclopentadecane (L2), containing a direct link between the ferrocene redox centre and respectively benzo-15-crown-5 and N-phenylaza-15-crown-5, have been prepared. The sodium cation forms 1:1 stoicheiometric complexes with both ionophores whereas the larger potassium cation produces 1:2 intermolecular sandwich complexes with the same ligands, which were also observed by fast-atom-bombardment mass spectrometry. Single-crystal X-ray structures of L1 and of its sodium complex [NaL1]PF6 have also been determined. Electrochemical investigations reveal that the binding of Na+, K+, and Mg2+ guest cations by L1 and L2 results in shifts of the respective ferrocene-ferrocenium redox couple to more positive potentials. The magnitude of these one-wave anodic shifts is related to the charge: radius ratio of the cationic guest species.